Factors Impacting Youth Development in Haiti - Justesen, Michael; Verner, Dorte (World Bank, Washington, DC, 2012)
Of the 1.6 million Haitian youth aged 15-24, only 13 percent are content with their lives. More than half of 20-year-olds have not completed secondary education and nearly half of youth in the labor market are unemployed. This paper investigates protective and risk factors predisposing youth to positive and negative behaviors. These factors, including poverty, gender, education, labor market, migration, family, health, and violence, are examined by using statistics and probability models based on Haiti's first household living conditions survey. Key findings show that female youth need special attention because they are more likely than their male peers to drop out of school and to be unemployed or inactive. Role models, guidance, expectations, and contacts in the form of parents or household heads are decisive factors in keeping youth in school, and to some extent, in their finding employment. In addition, domestic migration has a negative impact on the probability of being unemployed or inactive (positive self-selection), while marriage, drug abuse, and domestic violence increase the probability of dropping out of school.